High Magnetic Field Magneto-optics on Plasmonic Silica-Embedded Silver Nanoparticles - Gabbani, Alessio; Campo, Giulio; Bonanni, Valentina; van Rhee, Peter; Bottaro, Gregorio; de Julián Fernández, César; Bello, Valentina; Fantechi, Elvira; Biccari, Francesco; Gurioli, Massimo; Armelao, Lidia; Sangregorio, Claudio; et al. (Journal of physical chemistry. C, 2022)
Tuning the plasmonic response with an external magnetic field is extremely promising to achieve active magnetoplasmonic devices, such as next generation refractometric sensors or tunable optical components. Noble metal nanostructures represent an ideal platform for studying and modeling magnetoplasmonic effects through the interaction of free electrons with external magnetic fields, even though their response is relatively low at the magnetic field intensities commonly applied in standard magneto-optical spectroscopies. Here we demonstrate a large magnetoplasmonic response of silver nanoparticles by performing magnetic circular dichroism spectroscopy at high magnetic fields, revealing a linear response to the magnetic field up to 30 T. The exploitation of such high fields allowed us to probe directly the field-induced splitting of circular plasmonic modes by performing absorption spectra with static circular polarizations, giving direct experimental evidence that the magneto-optical activity of plasmonic nanoparticles arises from the energy shift of field-split circular magnetoplasmonic modes.